2003
DOI: 10.1210/jc.2002-021663
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Knife Radiosurgery in Acromegaly: A 4-Year Follow-Up Study

Abstract: Stereotactic radiosurgery by gamma-knife (GK) is an attractive therapeutic option after failure of microsurgical removal in patients with pituitary adenoma. In these tumors or remnants of them, it aims to obtain the arrest of cell proliferation and hormone hypersecretion using a single precise high dose of ionizing radiation, sparing surrounding structures. The long-term efficacy and toxicity of GK in acromegaly are only partially known. Thirty acromegalic patients (14 women and 16 men) entered a prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(127 citation statements)
references
References 41 publications
12
109
0
3
Order By: Relevance
“…In our patients, as in another recently published series of acromegalic patients treated with GK, remission rate was about 20% with a follow-up of about 48 months (25,26). In the present study in CD, the mean time to remission was 22 vs 36 months in our patients with acromegaly (25).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our patients, as in another recently published series of acromegalic patients treated with GK, remission rate was about 20% with a follow-up of about 48 months (25,26). In the present study in CD, the mean time to remission was 22 vs 36 months in our patients with acromegaly (25).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies suggested that the pre-GK somatostatin agonist (24) treatment had a radioprotective effect (24) and some did not (25,26). We found a significantly higher proportion of uncured patients in the group with anticortisolic drug at the time of GK than in the group without medical therapy.…”
Section: Discussionmentioning
confidence: 52%
“…Overall radiation-based treatment in mixed series induces hypopituitarism in almost half of the patients over a long follow-up (Jallad et al 2007). In cohorts treated solely with stereotactic methods variable rates of hypopituitarism have been reported from below 10% at 3.8 years (Attanasio et al 2003) to 31% at 8 years (Lee et al 2014a), 12-20% in most series (Milker-Zabel et al 2001, Pollock et al 2002, Wilson et al 2013, especially in large tumor masses (Pollock et al 2002, Beauregard et al 2003. Owing to the possibility of late hypopituitarism, long-term follow-up and periodic testing are mandatory after RT.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Stereotactic radiosurgery, on the other hand, is single-dose treatment that is an effective method of delivering radiation treatment to GH-secreting tumours, whilst minimising the risk of radiation to surrounding tissues. Available data suggest that pituitary hypersecretion may resolve faster with stereotactic radiosurgery, but long-term data are still awaited (14,15). Recent advances in medical treatment have raised the prospect of obtaining biochemical control in virtually every subject, with consequent relief of symptoms and restoration of life expectancy to normal.…”
Section: Introductionmentioning
confidence: 99%